(untitled) (Research, Society and Development, 2022)
Childhood obesity is a serious public health problem worldwide, because it is a chronic, non-communicable disease that affects a large part of the population regardless of gender, social class and age, a disease of multifactorial causes that is characterized mainly by the generalized accumulation of fat. However, despite the factors already investigated as genetic, cultural, religious and behavioral, a variable little cited is the influence of microbiological agents in this process has been investigated in recent decades in order to understand if there is a relationship and in this sense were found some viral agents that were related to animal models and later to humans among these Adenovirus 36 has been identified as one of the main corroborators in the genesis of nutritional and metabolic disorders and childhood obesity. Therefore, this study aimed to perform a narrative review of the literature on the relationship between childhood obesity and adenovirus 36. In the search for articles it was possible to reach a total of 161 results, but after the screening 10 were selected for synthesis of the review and other authors were implemented to reinforce the ideas presented. It is concluded that childhood obesity remains a pathology of extreme relevance to health and that in addition to the factors already known there is evidence of a relationship between adv 36 and obesity in children in different study populations.